Measurement of spring constants of various spring-mass systems by using smartphones: a teaching proposal - Erol, Mustafa; HocaoÃ„Å¸lu, Kadir; Kaya, Ã…Å¾eyda (Universitas PGRI Kanjuruhan Malang, 2020)
This study aims to develop a teaching proposal to measure spring constants of various spring-mass systems by means of the smartphones. Specifically, a single spring-mass system, a serial connected and a parallel connected spring systems are experi-mentally resolved, by using the ambient light sensor of the smartphones. The measurements are achieved by simply recording the light intensity, detected by the oscillating smartphone, as a function of time for the simple harmonic motion. Using the light intensity-time graphs, the average periods and eventually the spring constants are estimated and the outcomes are compared with the theoretical results. The overall outcomes of the work indicate some 3,3 % relative error for the serial connected springs and 10,8 % relative error for the parallel connected springs. The approach is important in the sense that the apparatus directly plots instantaneous momentum-time graphs and it creates an enjoyable and beneficial teaching atmosphere.